Evaluación de las prescripciones de antibióticos de los estudiantes de la clínica de la facultad de odontología de la Universidad Antonio Nariño sede Bucaramanga. (2021)
Infections that originate from resistant bacteria are a public health problem that is constantly increasing, since they are linked to many different causes, among which the incorrect use of antibiotics stands out.